Journal of Experimental & Clinical Cancer Research - Castelli, Mauro; Castelli, Alice; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Journal of Experimental & Clinical Cancer Research is an online peer-reviewed journal that publishes original research papers, reviews and commentaries in cancer research, from bench to bedside. Journal of Experimental & Clinical Cancer Research seeks manuscripts that include significant advances in basic cancer research and that offer a translational bridge from the laboratory to the clinic to open new avenues for the understanding, prevention, diagnosis and treatment of cancer. Specific areas of interest include, but are not limited to: mechanisms of progression of the malignant phenotype and metastatic disease; molecular alterations or biomarkers that predict response or resistance to treatment; translational research in targeted therapies; personalized medicine; tumor immunotherapy; large-scale molecular characterization of human tumors and innovative methods with potential applicability to clinical investigation. The following criteria provide an overview of the types of studies considered by the journal: Findings that have not been previously published in the same tumor model. Studies performed in multiple cell lines. Conclusions that are not representative of incremental findings. Studies that include a clearly written title and abstract that communicate the study's impact of significance to non-experts. The online appearance of Journal of Experimental & Clinical Cancer Research allows the immediate publication of accepted articles and the presentation of large amounts of data and supplemental information to ensure that new research is disseminated as efficiently and quickly as possible to the scientific community. Journal of Experimental & Clinical Cancer Research is the Official journal of the Regina Elena National Cancer Institute Owned by the Association for the Promotion of International Tumor Studies.
Keywords: Cancer; Immunology; Cell death; Oncology; Cancer Biology; Immunology; Cell Death; Oncology